Biochemical and Pharmacological Study of Venom from Centipede Scoropendra subspinipes mutilans Koch - Xun, Xiaohong; Li, Dan; Wu, Zhe; Liu, Lichao; Li, Xianlei; Liu, Yu (Asian Journal of Chemistry, 2013)
Almost all centipedes are predators and have venom glands. The primary purpose of centipede venoms is to kill or paralyze prey. Centipede venoms are complex chemical cocktails in which proteins are the main components. In this study, the biochemical and pharmacological properties of the venom of the centipede Scoropendra subspinipes mutilans Koch was investigated. The RP-HPLC and MALDI-TOF MS spectra of the venom indicated that it contains diverse peptides with molecular weights from 3000-10000 Da. Using the whole-cell patch-clamp, it was found that the venom could inhibit both voltage-gated sodium channels (VGSC) and potassium channels (VGPC) in adult rat dorsal root ganglion (DRG) neurons. Furthermore, pharmacological activities of the 43 fractions collected from RP-HPLC were examined on both VGSCs and VGPCs in rat DRG neurons. Consequently, we identified four fractions containing peptide neurotoxins which could inhibit VGSCs, as well as the other four fractions that containing peptide neurotoxins which could inhibit VGPCs. This study indicates that the venom of the centipede Scoropendra subspinipes mutilans Koch is indeed a rich source of novel pharmacologically interesting peptides that would receive increased attention from pharmacologists and biochemists in the future.